Extended-spectrum cephalosporin-resistant Escherichia coli isolated from chickens and chicken meat in Brazil is associated with rare and complex resistance plasmids and pandemic ST lineages - Casella, Tiago [UNESP]; Haenni, Marisa; Madela, Naiady Konno; Andrade, Leticia Kellen de; Pradela, Leticia Kalir; Andrade, Leonardo Neves de; Costa Darini, Ana Lucia da; Madec, Jean-Yves; Lelles Nogueira, Mara Correa (Oxford Univ Press, 2018)
Objectives: Brazil is the greatest exporter of chicken meat (CM) in the world. It is of utmost importance to monitor resistance to extended-spectrum cephalosporins (ESCs) in this sector because resistance to ESCs in Escherichia coli isolated from food-producing animals may contaminate humans through the food chain. Thus, the aim of this study was to characterize and compare ESC-resistant E. coli isolated from chickens and retail CM produced in south-eastern Brazil. Methods: Five CM samples and 117 chicken cloacal swabs (CCSs) were inoculated on MacConkey agar supplemented with cefotaxime. Presumptive E. coli colonies were identified and antimicrobial susceptibility was tested. Virulence and acquired bla(ESBL) and bla(AmpC) genes were sought and genetic environments characterized. Isolates were typed by phylogenetic grouping, XbaI-PFGE and MLST. Results: All five CM samples and 36 CCSs (30.8%) were positive for the presence of ESC-resistant E. coli, leading to the selection of 58 resistant isolates. ESC resistance was mostly due to the presence of the chromosome-encoded bla(CTX-M-2) gene, but plasmid-mediated bla(CTX-M-2), bla(CTX-M-8), bla(CTX-M-15), bla(CTX-M-55) and bla(CMY-2) were also detected. Multireplicon plasmids were sporadically identified, such as IncHI2/P-bla(CTX-M-2) and IncFII/N-bla(CTX-M-55). Phylogroup D predominated, while PFGE and MLST revealed a high genetic diversity. Conclusions: Live Brazilian chickens and CM act as reservoirs of ESC-resistant E. coli and resistance genes are located on highly diverse genetic determinants. Potentially pathogenic strains, which may represent a threat to human health and a source of environmental contamination, were also identified. Active surveillance is therefore essential in Brazil's chicken production line.